Reconceiving mothering motherhood in representations and in the lived experience - Baldo, Julienne Thesa Y.
This study explores the mother-as-subject discourse. It gives light to the following queries: a)What are the apparent and latent concepts of mothering vis-a-vis the popular concepts of the "ideal" life as represented in the mass medium of television? b)What are the lived experiences of rural mothers deal with patriarchal and socio-economic realities?and d)Considering the social context of mothering where there is patriarchy and an imbalanced global economy characterized by an unequal flow of "goods"/information from the"centers" to the "peripheries", what becomes of the mother, particularly her sense of self? The framework of the study weaves together discourses on patriarchy, capitalism, globalization, and gender and development vis-a-vis mothering. Consequently, it problematizes housewifery in particular, and the care economy in general. The study was conducted in Sitio Cataogan, Barangay Cawayan, Catarman, Province of Northern Samar, Region 8, Philippines. The primary respondents/research cooperators of the study were mothers who are exposed to television. From this population study of mothers, four research participants were chosen as cooperators for the life stories. This study first reviews the specific locale to be able to properly establish the context. a feminist content analysis of 20 Philippine television advertisements has been conducted to examine the utopian picture of motherhood, a reconception of motherhood could be made possible. Advertisements are analyzed because they are a powerful representation of the dominant groups' ideals. The primary data of the study are the life stories of four mothers. The personal interview is utilized as the data gathering method. The intention is to surface the lived experiences of women. The life story approach is seen as an effective way of engaging both the researcher and the women participants themselves in the exploration of lived realities. The introduction of the study states that development must be brought down to the personal level. The narration of the lives by The Mothers1 therefore, is the closest possible method of "voicing out" the composition of their lives. Likewise, the concept of a life being an improvisational form that is full of interruptions, conflicted priorities and exigencies can be best approximated by the life story method. Since this is a Women and Development Studies research, the development aspect of the study is found in the very act of The Mothers' telling of their stories...